Industrial training report: Majlis Daerah Tanjong Malim / Muhammad Amir Hakimi Roslan - Roslan, Muhammad Amir Hakimi (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This report provides details on the industrial training initiatives and the profile of Majlis Daerah Tanjong Malim (MDTM) organization. The duration of the training was approximately two months, starting on July 22, 2024, and ending on September 13, 2024. MDTM is the governing body in charge of overseeing and controlling Tanjong Malim and its adjacent areas in Perak, Malaysia. The council manages services in the local community including waste disposal, public buildings, city planning, and community growth. This report outlines the practical student's activities while undergoing training at MDTM. The MDTM library is a fantastic location for students to participate in industrial training due to its numerous departments and units, along with a substantial number of staff available to assist students with their tasks.